2014
DOI: 10.1590/s1981-77462014005000001
|View full text |Cite
|
Sign up to set email alerts
|

Características ideais do cirurgião-dentista na estratégia saúde da família

Abstract: Resumo O objetivo do presente estudo é conhecer a visão de integrantes das equipes da Estratégia Saúde da Família (ESF) sobre as características ideais de um cirurgião-dentista para atuar nesse modelo. O estudo foi do tipo qualitativo, utilizando a técnica de grupo focal para a coleta de dados. Foram realizados grupos focais com agentes comunitários de saúde, auxiliares de enfermagem, enfermeiras e médicos da ESF de Goiânia, Goiás, que haviam trabalhado com equipes de saúde bucal por um período mínimo de um an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…The basic curriculum of undergraduate dentistry in Brazil has been the subject of reformulations aiming at the change of the egress health professional, seeking to meet SUS needs. It is necessary that this professional presents skills and abilities built from his basic training, which should be in constant improvement 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The basic curriculum of undergraduate dentistry in Brazil has been the subject of reformulations aiming at the change of the egress health professional, seeking to meet SUS needs. It is necessary that this professional presents skills and abilities built from his basic training, which should be in constant improvement 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, low team interaction to plan combined oral health activities for vulnerable groups was observed (Q5). Concordances were obtained with other studies that discuss the challenge faced by Basic Health Care, from the perspective of the Family Health Strategy work to establish interdisciplinary work as a condition to promote integrality in health care and, consequently, to achieve satisfactory health outcomes [37][38][39]. A study carried out with family health teams in the city of Goiânia observed that professionals were not aware of how to perform health care beyond biomedical aspects.…”
Section: Discussionmentioning
confidence: 84%
“…A study carried out with family health teams in the city of Goiânia observed that professionals were not aware of how to perform health care beyond biomedical aspects. In addition, difficulties of interaction between dentists and the other members of health teams were observed due to the tendency of this professional to isolate himself in the office [38]. However, in southern Brazil, within the scope of the Family Health Strategy, another study verified a perception of teamwork associated with multiprofessionality, with the exchange of knowledge among members aiming at the implementation of health actions [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, the National Curricular Guidelines for Dentistry undergraduate courses came precisely to boost the transformation process in the opposite direction to the model 2 . Thus, professionals with a general professional vision coming from Dentistry school disciplines and sociobiological factors which determine oral diseases as well as health promotion, these dental professional would be better suited to future trends, human and ethical aspects [2][3] .…”
Section: Introductionmentioning
confidence: 99%